INNOVATIVE ASPECTS OF THE FORMATION AND DEVELOPMENT OF THE HIGH-TECH SECTOR OF THE NATIONAL ECONOMY - Tatiana Kolmykova; Oleg Artemyev (Вестник Северо-Кавказского федерального университета, 2022)
The article considers the problems of the development of high-tech sectors of the national economy in the face of fierce global competition and the struggle for limited resources. We investigated the role of government in the investment activity. Research of innovative aspects of the development of high-tech sector of the economy to determine the direction of industrial policy in the future, to identify priorities for the technical-tech development. Costs associated with the development and distribution industries in the high-tech sector of the national economy, should not be grounds for refusal of carrying out large-scale targeted industrial policy. On the contrary, in terms of international sanctions andfinancial constraints need to step up efforts to support the industries thatform the basis of a new technological order. It is their development in the foreseeable future is able to achieve sustainable economic growth parameters.